2023
DOI: 10.1021/acsami.2c20985
|View full text |Cite
|
Sign up to set email alerts
|

Noble Metal Nanoparticles Decorated Boron Nitride Nanotubes for Efficient and Selective Low-Temperature Catalytic Reduction of Nitric Oxide with Carbon Monoxide

Abstract: Parallel to CO2 emission, NO x emission has become one of the menacing problems that seek a simple, durable, and high-efficiency deNO x catalyst. Herein, we demonstrated simple syntheses of platinum group metal nanoparticle-decorated f-BNNT (PGM = Pd, Pt, and Rh, and f-BNNT stands for −OH-functionalized boron nitride nanotubes) as a catalyst for efficient and selective reduction of NO by CO at low-temperature conditions. PGM/f-BNNT with a low amount of noble metal nanoparticles (0.7–0.8 wt %) presents very e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Selective catalytic reduction of NO, an important branch of heterogeneous catalysis, plays an essential role in the catalytic purification of exhaust . It has been investigated intensively, such as the design of novel catalysts, the deactivation or resistance mechanism to SO 2 , H 2 O, and alkali metal, , building structure–activity relationships, ,, and the innovation in reaction mechanisms. ,, In-depth explorations in the latter two aspects are propitious for developing novel catalysts and facilitating the efficiency of researchers. , Effects of particle size on structure–activity relationships of NH 3 -SCR have been studied as well, mainly involving V 2 O 5 -WO 3 /TiO 2 , Fe or Cu/Zeolites, , and M/CeO 2 -γAl 2 O 3 (M = Pt, Pd, Rh) catalysts . However, these studies illustrated the role of the aggregation size of active components in activity and activating intermediates qualitatively rather than quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…Selective catalytic reduction of NO, an important branch of heterogeneous catalysis, plays an essential role in the catalytic purification of exhaust . It has been investigated intensively, such as the design of novel catalysts, the deactivation or resistance mechanism to SO 2 , H 2 O, and alkali metal, , building structure–activity relationships, ,, and the innovation in reaction mechanisms. ,, In-depth explorations in the latter two aspects are propitious for developing novel catalysts and facilitating the efficiency of researchers. , Effects of particle size on structure–activity relationships of NH 3 -SCR have been studied as well, mainly involving V 2 O 5 -WO 3 /TiO 2 , Fe or Cu/Zeolites, , and M/CeO 2 -γAl 2 O 3 (M = Pt, Pd, Rh) catalysts . However, these studies illustrated the role of the aggregation size of active components in activity and activating intermediates qualitatively rather than quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…Pt-modified catalysts with excellent low-temperature activity and high chemical and hydrothermal stability are widely used in catalytic reactions. For example, Chio et al synthesized platinum group metal nanoparticle-decorated boron nitride nanotubes as a catalyst for the efficient and selective reduction of NO by CO at low-temperature conditions. Ji et al reported negatively charged single-atom Pt-embedded catalysts which showed good SO 2 resistance in the selective catalytic reduction of NO x by CO.…”
Section: Introductionmentioning
confidence: 99%
“…The Lewis acid sites in the BNNT are assumed to interact with the oxygen of the cyclic carbonates, leading to the desolvation of Li + and hence providing free Li + responsible for enhanced Li-ion transport. Whereas, the defects sites in BNNT serve as binding sites for the anions, channelizing the transport of Li + during the charge/discharge process. , Moreover, due to the structural advantage of the BNNT, , commonly investigated for ion transport in fluid media the open-end hollow cylindrical structure allows the exhohedral and endohedral transport of Li + through electrostatic interactions. Hence, due to the multiple structural benefits, BNNT qualifies as an excellent electrolyte additive for LIBs.…”
mentioning
confidence: 99%